A Single Quantifiable Viral Load Is Predictive of Virological Failure in Human Immunodeficiency Virus (HIV)-Infected Patients on Combination Antiretroviral Therapy: The Austrian HIV Cohort Study. (15th June 2016) - Leierer, Gisela; Grabmeier-Pfistershammer, Katharina; Steuer, Andrea; Sarcletti, Mario; Geit, Maria; Haas, Bernhard; Taylor, Ninon; Kanatschnig, Manfred; Rappold, Michaela; Ledergerber, Bruno; Zangerle, Robert; ,; et al.
Abstract: Background.  Viral loads (VLs) detectable at low levels are not uncommon in patients on combination antiretroviral therapy (cART). We investigated whether a single quantifiable VL predicted virological failure (VF). Methods.  We analyzed patients receiving standard regimens with at least 1 VL measurement below the limit of quantification (BLQ) in their treatment history. The first VL measurement after 6 months of unmodified cART served as baseline VL for the subsequent analyses of the time to reach single VL levels of ≥200, ≥400, and ≥1000 copies/mL. Roche TaqMan 2.0 was used to quantify human immunodeficiency virus-1 ribonucleic acid. Factors associated with VF were determined by Cox proportional hazards models. Results.  Of 1614 patients included in the study, 68, 44, and 34 experienced VF ≥200, ≥400, and ≥1000 copies/mL, respectively. In multivariable analyses, compared with patients who were BLQ, a detectable VL ≤ 50 and VL 51–199 copies/mL predicted VF ≥ 200 copies/mL (hazards ratio [HR] = 2.19, 95% confidence interval [CI] = 1.06–4.55 and HR = 4.21, 95% CI = 2.15–8.22, respectively). In those with VL 51–199 copies/mL, a trend for an increased risk of VF ≥400 and VF ≥1000 copies/mL could be found (HR = 2.13, 95% CI = 0.84–5.39 and HR = 2.52, 95% CI = 0.96–6.60, respectively). Conclusions.  These findings support closer monitoring and adherence counseling for patients with a single measurement of quantifiable VL <200 copies/mL.